Demotic and "democratic" languages in post-independence Brazil, 1822-48. Issue 2 (3rd May 2020) - Paquette, Gabriel
ABSTRACT: This article addresses how the political language of democracy was used in nineteenth-century Brazil prior to 1850 and how its deployment was connected to related yet distinct political concepts, particularly liberalism and republicanism. It explores the prevalence of the language of democracy in a constitutional monarchy predicated on a socio-political order that was itself dependent on slavery and in which the vast majority of subjects, enslaved and free, were either de facto or de jure disenfranchised or excluded from the political process. The article focuses on the political ideas of the rebellions of the 1820s-40s, which mainly occurred in the provinces far from the capital of Rio de Janeiro, including the Confederation of the Equator, the Sabinada, the Farroupilha, and the Praieira.